Sodium-ion battery positive electrode material precursor as well as preparation method and application thereof
The HxMyLz(PO4)4 precursor prepared by liquid phase reaction method achieves uniform atomic mixing of metal elements and phosphorus elements, solving the problem of insufficient performance of the positive electrode material of sodium ion battery in the prior art, and improving electrochemical performance and magnification Performance, and simplify production processes and reduce costs.
Patent Information
- Application Number
- CN202411267848.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
In the preparation method of existing sodium ion battery positive electrode materials, it is difficult to achieve atomic uniformity by mixing between metal elements and molecular levels of metal elements and phosphorus elements, resulting in a decrease in sodium ion conductivity and lack of high-rate performance.
The metal element and phosphorus element were pre-combined by liquid phase reaction method to prepare HxMyLz(PO4)4 precursor, achieving uniform atomic mixing of metal elements and phosphorus elements, and mixing with Na source and carbon source and high-temperature sintering to prepare Na4MyLz( PO4)2P2O7/C positive electrode material.
It improves the electrochemical performance and rate performance of the cathode material, simplifies the production process, reduces the cost of raw materials, and is suitable for large-scale mass production.
Smart Images

Figure CN119118090A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a polyanion sodium ion battery positive electrode material precursor and a preparation method thereof, as well as application of the precursor in the preparation of positive electrode materials. Background Art
[0002] Due to the rich sodium resources, low cost, good low temperature performance and other advantages, sodium ion batteries have received widespread attention and are considered to be an ideal large-scale energy storage application technology. The iron-based phosphate pyrophosphate complex Na4Fe3(PO4)2P2O7 in the positive electrode material of polyanion sodium ion batteries has the advantages of high structural stability, good safety performance, and high cycle stability. On the basis of this material, further doping with Mn (such as Na4Fe x Mn y (PO4)2P2O7), which can further increase the working voltage of the material (with a voltage platform of 4V), thereby increasing the energy density of the battery. This type of material is currently a research hotspot in the positive electrode materials of sodium ion batteries.
[0003] The existing method for preparing polyanionic positive electrode materials is usually a high-temperature solid phase reaction method. For example, Chinese patent ZL202311118348.6 discloses mixing and grinding a sodium source compound, an iron source compound, a manganese source compound and a phosphorus source compound, and sintering to obtain Na4Fe x Mn y (PO4)2P2O7 positive electrode material. However, in this conventional solid-phase reaction preparation method, multiple raw material salts are mixed by physical grinding, which has the disadvantages of uneven dispersion and poor material consistency; and the metal elements (such as iron and manganese) and the metal elements and phosphorus are only mixed at the molecular level, and it is difficult to achieve uniform mixing at the atomic level between the elements, resulting in reduced sodium ion conductivity and lack of high-rate performance of the material. Summary of the invention
[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a polyanion positive electrode material precursor, and a preparation method thereof and application in the preparation of positive electrode materials for sodium ion batteries. The precursor pre-combines the required metal elements and phosphorus elements in a suitable proportion into a compound molecule by means of a liquid phase reaction, achieving uniform mixing between metal elements in the molecule and between metal elements and phosphorus elements at the atomic level, which is conducive to promoting the improvement of the electrochemical performance and rate performance of the positive electrode material prepared by the precursor.
[0005] In a first aspect of the present invention, a polyanionic cathode material precursor is provided, the chemical composition of which is H x M y L z(PO4)4, where M is Fe and / or Mn, L is one or more of V, Ti, Mg, Cr, Zr, 2 < x < 5, 2.6 ≤ y ≤ 3, 0 ≤ z ≤ 0.4; when M is Fe and Mn, the molar ratio of Fe:Mn = 1:9 to 9:1.
[0006] In the second aspect of the present invention, a method for preparing the precursor is provided, which is prepared by a liquid-phase heating reaction method.
[0007] In the third aspect of the present invention, an application of the precursor in a cathode material for a Na-ion battery is provided. Mix the precursor H x M y L z (PO4)4 with a Na source and a carbon source, and prepare a Na4M y L z (PO4)2P2O7 / C cathode material by high-temperature sintering.
[0008] Specifically, the method for preparing the polyanionic cathode material precursor includes:
[0009] Add a certain mass of M source, L source and phosphorus source to water and mix evenly to obtain a mixed solution with a solid content range of 10 - 60 wt.%, add acid to adjust the pH value of the mixed solution to 0.5 - 2, then heat the mixed solution to 80 - 250 °C and react for 4 - 48 h, and finally collect the precipitate and dry it to obtain the H x M y L z (PO4)4 precursor.
[0010] The acid is one or more of oxalic acid, lactic acid, acetic acid, malic acid, and citric acid.
[0011] Preferably, the Fe source compound in the M source is one or more of iron citrate, iron acetylacetonate, and Fe2O3; the Mn source compound is one or more of manganese citrate, manganese acetylacetonate, and Mn2O3. The phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate. The L source is not necessarily added. If added, the L source is an oxide or carbonate of the highest valence state of the transition metal elements V, Ti, Mg, Cr, Zr, such as one or more of V2O5, TiO2, MgO, MgCO3, CrO3, and ZrO2.
[0012] In the above preparation method, the drying method can be one of static heating drying, spray drying, and freeze drying, and the drying temperature is 100 - 300 °C.
[0013] The purpose of drying is, on the one hand, to remove the crystal water impurities present in the precursor product generated by the reaction through heating, and to promote H x My L z The crystals of the (PO4)4 precursor material grow fully and have a complete crystal form, which further promotes the complete crystal structure of the prepared polyanion positive electrode material and better electrical performance. On the other hand, it is convenient for batch production of standardized raw material products with a suitable Fe / P ratio, which is easy to store, transport and industrially promote and apply after drying, and is suitable for large-scale mass production of polyanion sodium-ion battery positive electrode materials.
[0014] With this H x M y L z The method for using (PO4)4 precursor to prepare the positive electrode material of polyanion sodium ion battery is as follows:
[0015] The dried H x M y L z The (PO4)4 precursor and the sodium source are mixed in a solvent to satisfy the Na:P molar ratio range of (0.98-1.10):1, and an organic carbon source is added or not added according to the different M sources used in preparing the precursors for sand milling and mixing, and after grinding to a particle size of 0.2-0.5 μm, spray drying is performed to obtain a mixed powder, and finally the powder is placed in an inert atmosphere, a reducing atmosphere or a non-oxidizing atmosphere, heated to 450-650°C at a heating rate of 0.5-5°C / min, and kept warm for 4-20 hours to obtain a polyanion type sodium ion battery positive electrode material Na4M y L z (PO4)2P2O7 / C (2.6≤y≤3, 0≤z≤0.4).
[0016] When the M source used is an organic metal compound, no additional organic carbon source is needed; when the M source is an inorganic metal compound, the amount of organic carbon source added accounts for 15 to 30 wt.% of the total mass of the material; when the M source is an inorganic and organic mixed metal source, the amount of organic carbon source added accounts for 5 to 25 wt.% of the total mass of the material.
[0017] The organic carbon source can be selected from one or more of glucose, sucrose, PEG, cyclodextrin, phenolic resin, oxalic acid, ascorbic acid, formaldehyde, acetaldehyde, n-butyraldehyde, lactic acid, citric acid, malic acid, oxalic acid, adipic acid, soluble starch, ascorbic acid, and EDTA.
[0018] The solvent can be selected from one or more of water, ethylenediamine, cyclohexane, acetone, methanol, ethanol, propanol, isopropanol, ethylene glycol, and n-butanol.
[0019] The sodium source compound can be selected from one or more of sodium carbonate, sodium bicarbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium hydroxide, sodium formate, sodium acetate, and sodium citrate.
[0020] The inert atmosphere may be nitrogen or argon, the reducing atmosphere may be nitrogen-hydrogen mixed gas or argon-hydrogen mixed gas, and the non-oxidizing atmosphere may be carbon dioxide (CO2).
[0021] The beneficial effects of the present invention are as follows:
[0022] 1. The present invention provides a precursor H of a polyanion type sodium ion battery positive electrode material x M y L z (PO4)4 and a preparation method thereof. The precursor is prepared by a liquid phase reaction method, wherein M and P of the three elements Na, M and P required for the polyanion positive electrode material are pre-combined by chemical reaction to form a standardized precursor raw material, and then a suitable proportion of Na source compound and carbon source are mixed, and then further sintered to prepare the polyanion sodium ion battery positive electrode material Na4M y L z (PO4)2P2O7 / C.
[0023] 2. Through the liquid phase reaction method, the prepared precursor combines the two elements M and P in appropriate proportions into a compound molecule through chemical methods, and pre-realizes the uniform combination of M and P elements at the atomic level. Compared with the conventional method of physically mixing separate sodium salts, metal salts and phosphate salts, the uniform mixing of metal elements and metal elements and phosphorus elements at the atomic level can promote the efficient conduction of Na ions inside the crystal, which is beneficial to improving the physical purity and high-rate performance of the material.
[0024] 3. H prepared by liquid phase reaction x M y L z Using (PO4)4 precursor as raw material is conducive to simplifying the production process of polyanion positive electrode materials. Since M and P atoms have been pre-combined and dispersed in the molecule through chemical reaction, and the liquid phase reaction process is easy to control the particle size, it is conducive to obtaining small particle products. Therefore, the grinding and dispersion time of the nanomill can be shortened to a certain extent, and the consistency of product performance indicators can be improved.
[0025] 4. The method for preparing the precursor is simple, the cost of raw materials is low, and there are a wide range of raw materials to choose from. Inorganic iron / manganese sources, organic iron / manganese sources, or inorganic-organic mixed iron / manganese sources can be used. The use of organic metal sources can further save the amount of carbon source added during the material preparation process and save production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 According to Example 1, H 3.3 Fe 1.74 Mn 1.16Na4Fe prepared by supplementing Na source with (PO4)4 precursor 1.74 Mn 1.16 XRD pattern of (PO4)2P2O7 / C.
[0027] Figure 2 The Na4Fe prepared according to Example 1 and Comparative Example 1 1.74 Mn 1.16 Comparison of charge and discharge curves of (PO4)2P2O7 / C at 0.1C rate.
[0028] Figure 3 The Na4Fe prepared according to Example 1 and Comparative Example 1 1.74 Mn 1.16 Comparison of (PO4)2P2O7 / C material after 150 cycles at 1C rate.
[0029] Figure 4 The Na4Fe prepared according to Example 4 and Comparative Example 4 2.95 Mg 0.02 Ti 0.03 Comparison of 1C rate charge and discharge curves of (PO4)2P2O7 / C positive electrode materials.
[0030] Figure 5 The electrical performance of Example 4 and Comparative Example 4 at different magnifications is compared. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below by examples in conjunction with the accompanying drawings so that those skilled in the art can easily understand the advantages of the present invention based on the contents of this specification.
[0032] Example 1
[0033] Preparation of H 3.3 Fe 1.74 Mn 1.16 (PO4)4 precursor, add ferric citrate, Mn2O3 and H3PO4 in a molar ratio of 1.74:0.58:4 into a reactor containing water and mix well, add acetic acid, adjust the pH value of the mixed solution to 1, control the solid content of all materials in water to 30wt.%, then heat to 120℃, react for 10 hours, unload, and then dry at 180℃ for 2h to obtain H 3.3 Fe 1.74 Mn 1.16 (PO4)4 precursor.
[0034] Weigh a certain mass of H 3.3 Fe 1.74 Mn 1.16 The (PO4)4 precursor and Na2CO3 are mixed in methanol.3.3 Fe 1.74 Mn 1.16 The molar ratio of (PO4)4 was fixed at 2:1, and the Na2CO3 and H 3.3 Fe 1.74 Mn 1.16 The total mass of (PO4)4 in methanol was controlled to have a solid content of 40 wt.%, and then the mixture was ground in turn with a basket grinder and a nano sand mill at room temperature until the particle size was 400 nm. The ground material was spray dried, and the dried powder was placed in a tube furnace, heated to 550°C at a heating rate of 3°C / min in a N2 atmosphere, and calcined for 10 hours to obtain Na4Fe 1.74 Mn 1.16 (PO4)2P2O7 / C positive electrode material, carbon content is 3.8wt.%.
[0035] Figure 1 is the XRD spectrum of the prepared positive electrode material, which can be seen to be basically consistent with the standard card (pdf no.89-0579).
[0036] Figure 2 The charge and discharge curve of the positive electrode material shows that in the voltage range of 2-4V, the first discharge capacity at 0.1C rate is 106.89mAh / g, while the Na4Fe prepared in Comparative Example 1 1.74 Mn 1.16 The first discharge capacity of (PO4)2P2O7 / C (dashed line) under the same conditions is only 95.58 mAh / g. Figure 3 The Na4Fe prepared according to Example 1 and Comparative Example 1 1.74 Mn 1.16 By comparing the cycle performance of (PO4)2P2O7 / C material at a high rate of 1C, it can be seen that the rate performance of the positive electrode material prepared according to Example 1 is much better than that of the material prepared in Comparative Example 1.
[0037] Comparative Example 1
[0038] Ferric citrate, Mn2O3, H3PO4 and Na2CO3 were mixed in methanol at a molar ratio of 1.74:0.58:4:2, and the solid content was controlled at 40wt.%. The mixed material was then ground in turn with a basket grinder and a nano sand mill at room temperature until the material particle size was 400nm. The ground material was spray dried, and the dried powder was placed in a tube furnace, heated to 550℃ at a heating rate of 3℃ / min under N2 atmosphere, and calcined for 10h to obtain Na4Fe 1.74 Mn 1.16 (PO4)2P2O7 / C positive electrode material, carbon content is 3.7wt.%. Figure 2The middle dotted line is the charge and discharge curve of the comparative material, and the first discharge specific capacity is 95.58 mAh / g.
[0039] Example 2
[0040] Preparation of H 3.42 Fe2Mn 0.86 (PO4)4 precursor, ferric acetylacetonate, Mn2O3 and H3PO4 were added to a reactor containing water in a molar ratio of 2:0.43:4 and mixed evenly, lactic acid was added, the pH value of the mixed solution was adjusted to 1.5, the solid content of all materials in water was controlled to 30wt.%, and then heated to 150℃, reacted for 10 hours, unloaded, and then dried at 160℃ for 2h to obtain H 3.42 Fe2Mn 0.86 (PO4)4 precursor.
[0041] Weigh a certain mass of H 3.42 Fe2Mn 0.86 The (PO4)4 precursor and Na2CO3 are mixed in water. Na2CO3 and H 3.42 Fe2Mn 0.86 The molar ratio of (PO4)4 was fixed at 2:1, and the Na2CO3 and H 3.3 Fe 1.74 Mn 1.16 The total mass of (PO4)4 in methanol was controlled to have a solid content of 40 wt.%, and then the mixture was ground in turn with a basket grinder and a nano sand mill at room temperature until the particle size was 300 nm. The ground material was spray dried, and the dried powder was placed in a tube furnace, heated to 550°C at a heating rate of 3°C / min under N2 atmosphere, and calcined for 10 hours to obtain Na4Fe2Mn 0.86 (PO4)2P2O7 / C positive electrode material, carbon content is 4.0wt.%. After electrical performance test, the first discharge capacity at 0.1C rate is 105.3mAh / g. 0.86 The first discharge capacity of (PO4)2P2O7 / C is only 94.6 mAh / g.
[0042] Comparative Example 2
[0043] Ferrous acetylacetonate, Mn2O3, H3PO4 and Na2CO3 were mixed in water at a molar ratio of 2:0.43:4:2, and the solid content was controlled at 40wt.%. The mixed material was then ground in turn with a basket grinder and a nano sand mill at room temperature until the material particle size was 300nm. The ground material was spray dried, and the dried powder was placed in a tube furnace, heated to 550℃ at a heating rate of 3℃ / min under N2 atmosphere, and calcined for 10h to obtain Na4Fe2Mn 0.86 (PO4)2P2O7 / C positive electrode material, carbon content is 3.8wt.%. The first discharge specific capacity of the comparative material is 94.6mAh / g.
[0044] Example 3
[0045] Fe2O3, Mn2O3 and H3PO4 were added to a reactor containing water in a molar ratio of 1:0.4:4 and mixed evenly. Oxalic acid was added to adjust the pH value of the mixed solution to 0.8. The solid content of all materials in water was controlled to 30wt.%, and then heated to 130°C. After reacting for 8 hours, the material was unloaded and then dried at 150°C for 2h to obtain H 3.6 Fe2Mn 0.8 (PO4)4 precursor.
[0046] Weigh a certain mass of H 3.6 Fe2Mn 0.8 The (PO4)4 precursor and Na2CO3 are mixed in water. Na2CO3 and H 3.6 Fe2Mn 0.8 The molar ratio of (PO4)4 was fixed at 2:1, and then organic carbon sources glucose and PEG20000 were added. The total weight of the organic carbon source accounted for 23wt.% of the total weight of the above four materials (glucose accounted for 8wt.%, PEG20000 accounted for 15wt.%), Na2CO3, H 3.6 Fe2Mn 0.8 The solid content of the total mass of (PO4)4 and the organic carbon source in water was controlled at 40wt.%, and then the mixture was ground in turn with a basket grinder and a nano sand mill at room temperature until the particle size was 280nm. The ground material was spray dried, and the dried powder was placed in a tube furnace, heated to 550℃ at a heating rate of 2℃ / min under N2 atmosphere, and calcined for 10h to obtain Na4Fe2Mn 0.8 (PO4)2P2O7 / C positive electrode material, carbon content is 3.85wt.%. The first discharge capacity of the positive electrode material at 0.1C rate is 104.7mAh / g.
[0047] Comparative Example 3
[0048] Fe2O3, Mn2O3, H3PO4 and Na2CO3 were mixed in water at a molar ratio of 1:0.4:4:2, and then organic carbon sources glucose and PEG20000 were added, the total weight of the organic carbon source accounted for 23wt.% of the total weight of the above four materials (glucose accounted for 8wt.%, PEG20000 accounted for 15wt.%), the solid content of all materials was controlled at 40wt.%, and then the mixed materials were ground in turn with a basket grinder and a nano sand mill at room temperature until the material particle size was 280nm. The ground materials were spray dried, and the dried powder was placed in a tube furnace, heated to 550℃ at a heating rate of 2℃ / min under N2 atmosphere, and calcined for 10h to obtain Na4Fe2Mn 0.8 (PO4)2P2O7 / C positive electrode material, carbon content is 3.8wt.%. The first discharge specific capacity of the comparative material is 92.8mAh / g.
[0049] Example 4
[0050] Preparation of H 2.99 Fe 2.95 Mg 0.02 Ti 0.03 (PO4)4 precursor, Fe2O3, H3PO4, MgCO3 and TiO2 were added into a reactor containing water in a molar ratio of 1.475:4:0.02:0.03 and mixed evenly, lactic acid was added, and the pH value of the mixed solution was adjusted to 1. The solid content of all materials in water was controlled at 30wt.%, and then heated to 120℃, reacted for 6 hours, unloaded, and then dried at 180℃ for 2h to obtain H 2.99 Fe 2.95 Mg 0.02 Ti 0.03 (PO4)4 precursor.
[0051] Weigh a certain mass of H 2.99 Fe 2.95 The (PO4)4 precursor and Na2CO3 are mixed in water. Na2CO3 and H 2.99 Fe 2.95 The molar ratio of (PO4)4 was fixed at 2:1, and then organic carbon sources glucose and PEG20000 were added. The total weight of the organic carbon source accounted for 24wt.% of the total weight of the above four materials (glucose accounted for 8wt.%, PEG20000 accounted for 16wt.%), Na2CO3, H 3.14 Fe 2.9The solid content of the total mass of (PO4)4 and the organic carbon source in water was controlled at 40wt.%, and then the mixture was ground in turn with a basket grinder and a nano sand mill at room temperature until the particle size was 280nm. The ground material was spray dried, and the dried powder was placed in a tube furnace, heated to 550℃ at a heating rate of 3℃ / min under N2 atmosphere, and calcined for 10h to obtain Na4Fe 2.95 Mg 0.02 Ti 0.03 (PO4)2P2O7 / C positive electrode material, carbon content is 3.9wt.%. The obtained positive electrode material has a discharge capacity of 101.01mAh / g at 1C rate, while the material prepared in comparative example 4 has a discharge capacity of 92.8mAh / g at 1C rate. Figure 4 ). Figure 5 The electrical properties of the materials prepared in Example 4 and Comparative Example 4 at different rates are compared. It can be seen that the high rate performance of the positive electrode material prepared in Example 4 is better than that of Comparative Example 4.
[0052] Comparative Example 4
[0053] Fe2O3, H3PO4, MgCO3, TiO2 and Na2CO3 were mixed in water at a molar ratio of 1.475:4:0.02:0.03:2, and then organic carbon sources glucose and PEG20000 were added. The total weight of the organic carbon source accounted for 23wt.% of the total weight of the above four materials (glucose accounted for 8wt.%, PEG20000 accounted for 16wt.%), and the solid content of all materials was controlled at 40wt.%. Then, the mixed materials were ground in turn with a basket grinder and a nano sand mill at room temperature until the material particle size was 280nm. The ground materials were spray dried, and the dried powder was placed in a tubular furnace, heated to 550°C at a heating rate of 2°C / min under N2 atmosphere, and calcined for 10h to obtain Na4Fe 2.95 Mg 0.02 Ti 0.03 (PO4)2P2O7 / C positive electrode material, carbon content is 3.8wt.%. The discharge specific capacity of the comparative material at 1C rate is 96mAh / g.
[0054] It should be noted that the purpose of publishing the embodiments is to further help understand the connotation and extension of the present invention, but those skilled in the art can understand that various substitutions and modifications are possible without departing from the scope of the present invention and the appended claims. Therefore, the present invention should not be limited to the contents disclosed in the embodiments, and the scope of protection claimed by the present invention shall be subject to the scope defined in the claims.
Claims
1. A polyanion cathode material precursor, the chemical composition of which is H x M y L z (PO4)4, wherein M is Fe and / or Mn, L is one or more of V, Ti, Mg, Cr, Zr, 2 <x<5,2.6≤y≤3,0≤z≤0.4。 2. The polyanionic cathode material precursor according to claim 1, characterized in that: M is Fe and Mn, with a molar ratio of Fe:Mn=1:9 to 9:
1.
3. A method for preparing a polyanionic cathode material precursor according to claim 1 or 2, comprising: The M source, L source and phosphorus source are added into water and mixed evenly to obtain a mixed solution with a solid content in the range of 10 to 60 wt.%, an acid is added to adjust the pH value of the mixed solution to 0.5 to 2, and then the mixed solution is heated to 80 to 250° C. to react for 4 to 48 hours, and finally the precipitate is collected and dried to obtain the polyanionic positive electrode material precursor.
4. The preparation method according to claim 3, characterized in that: The acid is selected from one or more of oxalic acid, lactic acid, acetic acid, malic acid and citric acid.
5. The preparation method according to claim 3, characterized in that: The Fe source compound in the M source is selected from one or more of ferric citrate, ferric acetylacetonate, and Fe2O3; the Mn source compound in the M source is selected from one or more of manganese citrate, manganese acetylacetonate, and Mn2O3; the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.
6. The preparation method according to claim 3, characterized in that: The L source is the highest valence state oxide or carbonate of transition metal elements V, Ti, Mg, Cr and / or Zr.
7. A method for preparing a positive electrode material for a sodium ion battery, comprising: x M y L z (PO4)4 was mixed with sodium source and carbon source and sintered at high temperature to obtain the polyanion type sodium ion battery positive electrode material Na4M y L z (PO4)2P2O7 / C, wherein M is Fe and / or Mn, L is one or more of V, Ti, Mg, Cr, Zr, 2 <x<5,2.6≤y≤3,0≤z≤0.4。 8. The method according to claim 7, characterized in that The following steps are involved: 1) Obtaining the polyanionic cathode material precursor according to the preparation method according to any one of claims 3 to 6; 2) Mixing the polyanionic cathode material precursor obtained in step 1) with a sodium source in a solvent to satisfy a Na:P molar ratio of (0.98-1.10):1, and adding or not adding an organic carbon source according to the different M sources used in step 1), and then grinding and mixing by sand milling to a particle size of 0.2-0.5 μm; wherein, when the M source used is an organic metal compound, no organic carbon source is added; when the M source is an inorganic metal compound, the amount of the organic carbon source added accounts for 15-30 wt.% of the total mass of the material; When the M source is an inorganic and organic mixed metal source, the amount of organic carbon source added accounts for 5 to 25 wt.% of the total mass of the material; 3) spray drying the ground material to obtain a mixed powder, placing the powder in an inert atmosphere, a reducing atmosphere or a non-oxidizing atmosphere, heating to 450-650° C. for 4-20 hours to obtain a polyanion sodium ion battery positive electrode material Na4M y L z (PO4)2P2O7 / C.
9. The method according to claim 8, characterized in that The sodium source is selected from one or more of sodium carbonate, sodium bicarbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium hydroxide, sodium formate, sodium acetate, and sodium citrate; the organic carbon source is selected from one or more of glucose, sucrose, PEG, cyclodextrin, phenolic resin, oxalic acid, ascorbic acid, formaldehyde, acetaldehyde, n-butyraldehyde, lactic acid, citric acid, malic acid, oxalic acid, adipic acid, soluble starch, ascorbic acid, and EDTA.
10. The method according to claim 8, characterized in that The solvent in step 2) is selected from one or more of water, ethylenediamine, cyclohexane, acetone, methanol, ethanol, propanol, isopropanol, ethylene glycol, and n-butanol; the inert atmosphere in step 3) is nitrogen or argon; the reducing atmosphere is a nitrogen-hydrogen mixed gas or an argon-hydrogen mixed gas; and the non-oxidizing atmosphere is carbon dioxide.
Citation Information
Cited By
Preparation method of low-cost high-performance sodium-ion battery cell
CN120674610A
